PENINGKATAN KREATIFITAS SANTRI MELALUI PROGRAM PENGOLAHAN TANAMAN HIDROPONIK - Siti Sukaesih; Ipah Ismayati; Meilinda Lestari; Gheby Ameli Widiyah; Ibrahim Rasyid Zamzami (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2019)
This article aims to identify hydroponic methods that are most effective and efficient in the context of agricultural systems, and provide educational assistance for students to become entrepreneurs by seeing the potential in the environment that can be used to conduct business opportunities. The method of this study used a qualitative approach. The result of this study showed that hydroponic plants are plants using very practical methods. This plant does not require a large area and its maintenance is so easy. This hydroponic planting technique is very suitable for use in areas that have lost a lot of land due to building or factory construction. This could be done in order to maintain the stability of nature where there is now a lot of vehicle pollution. Therefore, we also have to filter it by increasing the oxygen from green plants. In this study, we did not only discuss hydroponics, but also discussed entrepreneurship that we have learnt together with students at MA At-Tauhidiyah. Finally, they can be more productive in facing the Covid-19 pandemic.